2010
DOI: 10.1292/jvms.10-0172
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility and Methicillin Resistance in Staphylococcus pseudintermedius and Staphylococcus schleiferi subsp. coagulans Isolated from Dogs with Pyoderma in Japan

Abstract: ABSTRACT. To understand species distribution, trends of antimicrobial susceptibility and prevalence of methicillin resistance in canine staphylococci in Japan, 190 coagulase-positive staphylococci (CoPS) were isolated from dogs with pyoderma in 2 Japanese veterinary referral hospitals. Using a multiplex polymerase chain reaction (M-PCR) method, two CoPS species were identified: 170 Staphylococcus pseudintermedius (89.5%) and 20 S. schleiferi subsp. coagulans isolates (10.5%). In these isolates, susceptibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
82
4
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 38 publications
10
82
4
8
Order By: Relevance
“…The frequency of MRSP detected in the present study (94.3%) was much higher than those observed in similar studies (Medleau et al, 1986;Kania et al, 2004;Sasaki et al, 2007;Griffeth et al, 2008;Kawakami et al, 2010), which leads to an important concern in Veterinary Medicine in Brazil. Kawakami, et al (2010) also found a high percentage of MRSP isolates (66.5%) derived from dogs with pyoderma through the investigation of the mecA gene.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…The frequency of MRSP detected in the present study (94.3%) was much higher than those observed in similar studies (Medleau et al, 1986;Kania et al, 2004;Sasaki et al, 2007;Griffeth et al, 2008;Kawakami et al, 2010), which leads to an important concern in Veterinary Medicine in Brazil. Kawakami, et al (2010) also found a high percentage of MRSP isolates (66.5%) derived from dogs with pyoderma through the investigation of the mecA gene.…”
Section: Discussioncontrasting
confidence: 72%
“…Kawakami, et al (2010) also found a high percentage of MRSP isolates (66.5%) derived from dogs with pyoderma through the investigation of the mecA gene. Other studies evaluated isolates from healthy skin revealing smaller percentages (Hartmann et al, 2005;Fazakerley et al, 2010;Onuma et al, 2012), which may explain the differences in our results that evaluated isolates from clinical lesions (Table 1).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In Japan, 27 MRSP characterized by the growth on chromID MRSA agar and confirmed by the presence of mecA gene, in 200 cats and dogs, most of which were isolated from dogs (n: 25) [26] . Another study from Japan revealed 66.5% (113/170) as the prevalence of MRSP isolated from dogs based on the detection of mecA gene [27] . The prevalence of MRSP in Europe seems to be low as reported in Spain 4.6% (9/196) [6] , in Germany 7.4% (60/814) [7] and in Italy 2% (10/590) [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Superficial and deep bacterial pyoderma is one of the most common canine skin diseases caused by Staphylococcus pseudintermedius and less frequently by S. aureus and S. schleiferi (Bannoehr et al 2007;Sasaki et al 2007;Fitzgerald 2009;Kawakami et al 2010;Noli & Morris 2012), organisms that can also colonize in-contact humans, such as dog owners and veterinary personnel (Morris et al 2010;Weese & van Duijkeren 2010). The recent emergence of methicillin-resistant and multi-drug resistant S. pseudintermedius has reinforced the idea of preferring macrolides, lincosamides or potentiated sulfonamides instead of potentiated penicillins, cephalosporins or fluoroquinolones due to the lower potential of the former to induce bacterial resistance (Weese & van Duijkeren 2010;Cain et al 2011;Bond & Loeffler 2012).…”
Section: Introductionmentioning
confidence: 99%